Improved Immune Response to Recombinant Influenza Nucleoprotein Formulated with ISCOMATRIX - Cargnelutti, Diego Esteban (2012)
Current influenza vaccines elicit antibodies effective against homologous strains, but new strategies are urgently needed for protection against emerging epidemic or pandemic strains. Although influenza vaccine candidates based on the viral nucleoprotein (NP) or matrix protein do not elicit sterilizing immunity, they have the advantage of inducing immunity that may cover a larger number of viral strains. In this study, recombinant NP produced in Escherichia coli was purified and formulated in combination with the adjuvant ISCOMATRIX. This formulation increased a NP-specific immunity in mice, with a Th1 profile, and may constitute a promising low-cost influenza vaccine candidate, with ability to stimulate humoral and cellular immune responses.